Distribution and ecology of anurans at Sg. Moyog water catchment area, Crocker Range, Sabah - Yuta Inaguma (2019)
Water catchment areas are an important resource for providing a major ecosystem service to diversity and human living. However, it is also reported as a resident settlement center. Therefore, in order to understand the impact of population placement on these resources, studies on the ecological function of the irrigation in Sungai( =Sg) Moyog catchment have been conducted. Studies have focused on four different landscapes; forests, plantation, grasslands and dams. Visual sampling has been implemented and a total of 26 species including 9 additional new species have been recorded. Most irradiation shows the high dependence and richness of species in the forest. Additionally, the community has been confirmed differently in forest, plantation, grassland and dams (P = 0.03). This shows that land-use conversion has a negative impact on the community of anuran (r = 0.47, p < 0.001). Changes in the barometric aspect also showed a strong impact on the diversity of the irrigation compared to the conversion of soil (r = 0.35, p < 0.001). Land conversion observations using satellite images of WorldView2 showed an increase in land placement and development due to urbanization and plantation activities in the study area. Population placement is observed mostly in the downstream and upstream Moyog River. The species distribution model (SOM) has been created on the settlement of the population around the downstream river and finds the subdivision and composition of the community anakan is low. On the other hand, upstream is also a part of the community and the composition of the community is high. It is therefore unreasonable to suggest that the interests of ecosystem services are not understood, and human activities create a negative impact on the ecosystem. Generally speaking, although plantation is regarded as an appropriate landscape, it can maintain the community of anatomy, but, changes in the barometric aspect can have an impact on the variety of irrigation. Furthermore, the species distribution model also shows the biological marker dependent on water vapor pressure. Therefore, it can be concluded that the environment with good canopy coverage, high humidity and water vapor pressure is important to ensure community conservation and the subdivision of ecosystems.